(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
The lecture focuses on the main issues related to the use of algorithms and computational models in the realm of criminal proceedings. The analysis encompasses three main topics: the impact of software and models as means to intrude individuals’ privacy, in gathering evidence; the use of algorithm-generated data, used as evidence in trials; the compliance of computational models as decision-making instruments with fundamental rights.